ON PROFESSIONAL SUPERVISION IN SOCIAL WORK IN ROMANIA. GENERAL ASPECTS AND CHALLENGES DURING THE COVID-19 PANDEMIC - BODI, Diana-Cristina (Universitatea Transilvania Brasov, 2021)
This paper presents the results of qualitative research in terms of supervision in social work organizations during the COVID-19 pandemic. The data were collected by applying an interview guide, to which 22 social workers responded. The results of the research refer to how the measures taken during the pandemic affected social workers. It is also presented to what extent the supervision done within the organizations responded to the needs of social workers in this period of crisis. This research confirms the fact that supervision is an indispensable activity in social work organizations, especially in Romania, where, as a professional activity, it is still in the beginning.
Keywords: supervision in social work; burnout; COVID-19 pandemic